2021
DOI: 10.1302/0301-620x.103b6.bjj-2020-2003.r1
|View full text |Cite
|
Sign up to set email alerts
|

Robotic-assisted total knee arthroplasty improves accuracy and precision compared to conventional techniques

Abstract: Aims Robotic-assisted total knee arthroplasty (RA-TKA) is theoretically more accurate for component positioning than TKA performed with mechanical instruments (M-TKA). Furthermore, the ability to incorporate soft-tissue laxity data into the plan prior to bone resection should reduce variability between the planned polyethylene thickness and the final implanted polyethylene. The purpose of this study was to compare accuracy to plan for component positioning and precision, as demonstrated by deviation from plan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 32 publications
2
45
0
Order By: Relevance
“…As such, there have been several previous investigations into implant positioning, limb length and alignment, learning curve, postoperative outcomes, and cost-effectiveness with robotic arthroplasty with an attempt to demonstrate advantages. When compared to conventional jig-based TKA, robotic knee arthroplasty has been associated with increased accuracy, improved implant positioning, and a reduction in outliers [ 3 , [14] , [15] , [16] ]. However, this has not translated into clinical benefits for patients at midterm to long-term follow-up [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, there have been several previous investigations into implant positioning, limb length and alignment, learning curve, postoperative outcomes, and cost-effectiveness with robotic arthroplasty with an attempt to demonstrate advantages. When compared to conventional jig-based TKA, robotic knee arthroplasty has been associated with increased accuracy, improved implant positioning, and a reduction in outliers [ 3 , [14] , [15] , [16] ]. However, this has not translated into clinical benefits for patients at midterm to long-term follow-up [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Robotics in total joint arthroplasty (TJA) have several proposed benefits for surgeons and patients. Notably, robotic arm-assisted TJA have been shown to be more accurate than manual on radiographic evaluation of component position [ 3 , 4 ]. However, the evidence is variable, and robotics has yet to translate to improvements in clinical outcomes [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Whether robotic assistance has a more positive impact on early functional recovery after TKA remains controversial. RA-TKA has been widely reported to improve precision, provide better prosthesis position and lower extremity force lines, and obtain better imaging and functional outcomes than conventional surgery [ 1 3 ]. However, some studies have also concluded that there is no major difference in postoperative function and pain scores between robot-assisted and conventional manual total knee arthroplasty (CM-TKA) [ 4 – 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to robots, common assistive technologies include computer navigation and patient-specific cutting guides. There has been abundant evidence that computer navigation ( 35 , 36 ) and robots ( 37 , 38 ) can produce better precision and prosthesis alignment than conventional instrumentation but limited evidence that this translates into better long-term clinical outcomes. Patient-specific cutting guides also require customization.…”
Section: Discussionmentioning
confidence: 99%